2019
DOI: 10.18502/ijpho.v9i3.1170
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Childhood Cancer in Iran: A systematic review and meta-analysis

Abstract: Background: Childhood cancer (ChC) is very rare and occurs between birth and 14 years of age. There are several reports about ChC incidence from various regions of Iran, but with conflicting results.  The present study aimed to do a systematic review to estimate the accurate incidence rate of ChC among Iranian people. Materials and Methods: This systematic review was performed based on the preferred reporting items for systematic reviews and meta-analyses (PRISMA) checklist in 2018. A literature search w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…3 In a meta-analysis study, the lowest incidence rate in Iranian women is estimated at 0.4 per 100,000 people. 5 Factors such as differences in access to healthcare, late diagnosis, occupational exposure, pattern of Cigarette smoking, and the presence of steroid hormone in the two sexes 3 are the reasons for these discrepancies. Increasing age as a risk factor plays an important role in the incidence of BC.…”
Section: Gender and Agementioning
confidence: 99%
“…3 In a meta-analysis study, the lowest incidence rate in Iranian women is estimated at 0.4 per 100,000 people. 5 Factors such as differences in access to healthcare, late diagnosis, occupational exposure, pattern of Cigarette smoking, and the presence of steroid hormone in the two sexes 3 are the reasons for these discrepancies. Increasing age as a risk factor plays an important role in the incidence of BC.…”
Section: Gender and Agementioning
confidence: 99%
“…Similar to most LMICs, there are no precise statistics on childhood cancer in Iran [ 1 ]. The results of a systematic review showed that the incidence rate of pediatric cancer in Iran is 16.5 per 100,000, which is slightly higher than that in other countries [ 5 ]. Moreover, reports related to provincial registries indicate that leukemia (with a prevalence of 30%) is the most prevalent type of cancer among children in Iran, similar to other countries [ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These statistics roughly represent national figures, since MAHAK supports almost all children with cancer throughout the country. According to a recent Iranian study, the crude incidence of childhood cancer (0–14 years) was 16.8 per 100,000 for males and 16.56 per 100,000 for females [ 4 ].…”
Section: Introductionmentioning
confidence: 99%